Conceptions intuitives des notions de justice et de liberté : résultats d'une étude au collège dans le cours d'enseignement moral et civique - Emmanuel Sander; Géry Marcoux; Anouchka Wyss; Stéphanie Naud; Calliste Scheibling-Sève; Hippolyte Gros; Katarina Gvozdic (Nantes Université, 2022)
The development of critical thinking as a transversal skill has become an educational issue in many countries. Moreover, it seems crucial today to prepare students, who are already active members of society and the citizens of tomorrow, to have a critical outlook, in terms of an informed opinion regard-ing the values of the society in which they are immersed. In France, there is a moral and citizenship edu-cation program that aims to serve this purpose. However, it is also becoming increasingly clear that intuitive conceptions can hinder reflections and decision-making about social issues. Thus, improving one's knowledge of existing conceptions of essential notions in citizenship education such as justice and freedom should make it possible to go beyond one's preconceived ideas and shift one's perspec-tive. This is the subject of the study on which this article focuses.